STUDI EVALUASI DAN RENOVASI SISTEM PENTANAHAN DI SEKOLAH MENENGAH KEJURUAN (SMK) NEGERI 1 CIMAHI - Sunarto Sunarto; Toto Tohir; Robert Adriaan Philipus; Yudi Prana Hikmat; Trisnawiyana Trisnawiyana; Yoseph Santosa (MADANI: Jurnal Pengabdian Kepada Masyarakat, 2021)
This research is a follow-up to the findings of the inspection and grounding testing in PKM 2018 activities. The value obtained exceeds 5 ohms. This is not according to the standards based on the General Requirements for Electrical Installation (PUIL) 2011. In the 2019 PKM program activities, evaluation and renovation studies of the installed earthing system which includes: surveying the location to be grounded, drilling for the position of the electrodes to be installed, installation of electrodes equipped with Bentonic material which functions as a binder so that the electrodes with the ground become one and strong, measurement of the earthing value, perform grounding installation, re-measurement of earthing. The earthing value obtained is much smaller than the previous measurement results of 2.83 ohms in the Electronics Laboratory and 2.72 Ohms at the Automation Laboratory of SMKN 1 Cimahi. It is according to the recommended standard PUIL 2011. The PKM team proposes the management of SMKN 1 Cimahi to carry out a routine maintenance and measurement process twice a year on the newly installed earthing system so that the earthing value remains according to the standard.